ISOLASI DAN IDENTIFIKASI GOLONGAN KOMPONEN KIMIA AKTIF ANTIBAKTERI EKSTRAK N-BUTANOL SAWO MANILA (Achras zapota LINN.) ASAL KOTA PALOPO - Rusli, Rusli; Prayitno, Dedy (Jurnal Ilmiah As-Syifaa, 2017)
Sawo manila is one of the Zapotaceae family plant which have been investigated on n-butanol extract generate active spot as an antibacterial, therefore isolation and investigation of  which is necessary. The aim of the investigation was to identify the chemical group of antibacterial  active chemically. The methanol extract obtained by maceration method was 50 gram, continued by partition with diethyl eter obtained 17,3 gram dried extract, the residue ofiz then partition with n-butanol obtained 3,7 gram dried extract the extract of which isolated by conventional colomn cromotography method obtained 7 fractions. The second fraction on Bioautografi-TLC given antibacterial activity. Then the fraction  re-isollated  by preparative-TLC gained the second (2nd) band of which crystalzed by two dimention of TLC and multi eluen system. The single spot had positive reaction on the spot visualizer was alkaloid group with the maximum wavelength on 295,5 nm and the infra red spectra interpretation shown that amin group (NH) on wave value 1247 cm-1, 2361 cm-1, and 1294 cm-1 strengthen by secondary amin functional group (-NH-), within wave value 3447 cm-1 and 1294,26 cm-1,  aromatic CH group and the aromatic amin 1451 cm-1, unconjugated alkene group on 1652.32 cm -1 strengthen by alkene group on 2922,37 cm-1.